Preliminary bacteriological assessment of fresh milk produced by Caguyman Resource Development Dairy Cooperative - Bacanto, Leah D. (SOTECH, University of the Philippines in the Visayas, 1997)
A locally produced fresh milk product by the Caguyuman Resource Development Dairy Cooperative in Panay State Polytechnic College, Pontevedra, Capiz was assessed for its total bacterial count as well as coliform count.